Diabetic retinopathy screening in New Zealand requires improvement: results from a multi‐centre audit - Edward Hutchins; Kirsten J. Coppell; Ainsley Morris; Gordon Sanderson (Elsevier, 2012)
Abstract Objective: To determine whether diabetic retinal screening services and retinopathy referral centres in New Zealand meet the national guidelines for referral and assessment of screen detected moderate retinal and mild macular diabetic eye disease. Methods: Diabetic retinal screening pathways and the data collected at four main centre retinal screening services were described and compared with recommendations in the national diabetes retinal screening guidelines. A retrospective audit of photoscreen detected moderate retinopathy (grade R3), and mild maculopathy (grades M2B and M3) during May to August 2008 was undertaken. Data collected by retinopathy referral centres were used to examine the follow‐up of screen detected cases and to make comparisons with the national recommendations. Results : All four screening services used the guidelines for grading, but the recommended dataset was incomplete. Not all recorded data were readily accessible. The retinal photos of 157 (2.4%) patients were graded as R3, M2B, M3 or a combination. The proportion of those screened with these grades varied across the four centres from 1.2% to 3.4%. Follow‐up of the 157 screen positive patients did not always comply with guideline recommendations. Seventy five (48%) were referred for review by an ophthalmologist as recommended, 45 (60% of referred) were seen within the recommended six months. Nine patients (15% of the 60 with a documented assessment) were referred for or received laser treatment at 12‐months follow‐up. Conclusion: Quality diabetic retinal screening data systems and quality assurance programs are required to improve the monitoring and quality of retinal screening in New Zealand.